Navigating the spaces of children's spiritual experiences: influences of tradition(s), multidisciplinarity and perceptions. Issue 1 (2nd January 2019) - Adams, Kate
ABSTRACT: Children across the world report similar spiritual experiences. Empirical studies suggest that most resonate with the children's traditions; a finding which should, in theory, afford them a safe spiritual space. However, a number of factors can situate them in a less certain place. The paper uses the metaphors of trees imbued with different shades of light, from the vivid, shimmering and opaque to the invisible, to illustrate the types of spiritual spaces in which children find themselves. Their location is shaped in part by connection or disconnection with traditions, alongside wider cultural forces. Three navigation tools are used to show how children may move between these spaces: the spiritual experience and its relationship with traditions; the influences of multidisciplinary approaches; and children's perceptions of their experiences. The paper concludes that these metaphors and tools may be a useful way to understand the spiritual spaces in which children find themselves.